DESIGN OF A PID CONTROLLER EMBEDDED WITH TAGUCHI METHOD FOR PRECISE POSITIONING OF AN XY TABLE BALL SCREW DRIVE SYSTEM - Abdullah, L.; Kamaludin, K.N.; Mohamad, A.M.M.A.; Jamaludin, Z.; Nordin, M.H. (Journal of Advanced Manufacturing Technology (JAMT), 2022)
There are huge demands on producing high accuracy precision products, with a controller that is able to compensate the existence of disturbance forces, which consists of mechanical structures, mass variances, frictional forces, and cutting forces. The objective of this study is to further optimize PID controller to overcome the disturbance forces. Optimization method employed is the Taguchi method, for the purpose of tuning the proportional gain (KP), integral gain (KI) and derivative gain (KD) of the proposed controller. The controller is then performed experimentally on a real plant, consisting of an XY table ball screw drive system. The tracking performance of the controller is evaluated based on the maximum tracking error. The effectiveness of the proposed controller is determined by comparing the performance to the tuning method of the classical Ziegler-Nichols approach. The contribution of the study is the adaptation of Taguchi method with PID controller during tuning of the parameter. It shows a significant result, where minimum of 52 % improvement is observed over the classical Ziegler-Nichols tuned PID controller.